Kinerja Pelaksanaan Program Keluarga Harapan Berdasarkan Perspektif Balance Scorecard ( Studi Kasus Pada Kantor Dinas Sosial Kabupaten Bintan ) - Andila Putri Susanti (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
In 2007,Indonesia’s goverments runned a main project called Program Keluarga Harapan. The aim of this project is to build social insurance system for the pover. Even it has been running for 7 years since it was established, but in Bintan, it was running at 2010 by Dinas Sosial,instead. Based on that situation, this paper is made to describe the efectivity of organitation peformance measurement based on 4 perspectives of Balanced Scorecard. Using qualitative methods, those perspectives show us that Dinas Sosial still faces some problems running this project. In order to gain the project’s goal, the goverment should pay attention to each perspective in formulating their strategies. Keywords: Program Keluarga Harapan, performance measurement, Balanced Scorecard